Protecting the integrity of forensic psychological testing: a reply to geffner, et al. (2009) - Medoff D (Journal of Child Custody)
Recommendations regarding psychological test use made by Geffner, Conradi, Geis, and Aranda (2009) directly contradict well established standards of practice, guidelines promulgated by several professional organizations, and well-known legal standards regarding the admissibility of evidence in Court. This article refutes these recommendations and argues that test selection in the forensic context requires adherence to the principles enumerated in established case law as well as relevant ethical principles and standards of practice reflected in practice guidelines. Utilizing subjectively based and scientifically unreliable psychological assessment tools such as those recommended by Geffner and his colleagues introduces unknowable degrees of error, jeopardizes the integrity of evaluative methodologies in use, and seriously compromises the data that comprises the foundation upon which psychological opinions are rendered and legal decisions are made. In making their recommendations, these authors ignore an extensive and important body of empirical literature, professional practice guidelines, and legal rules requiring the use of scientifically supported, validated, and reliable test instruments for forensic use.